Computational clustering applied to mental models for understanding the Valley of Death in innovation processes - Jim Giraldo-Builes; René Yepes; Iván Rojas; Juan Carlos Bri\~nez-De León (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
The Valley of Death is the gap between the completion of research and development (R&D) projects and their transition to innovation. A key aspect to explain it are mindsets, which are one of the most complex to explain due to the number of factors they contain. What remains unclear is how people might have patterns of understanding the processes and activities that define mental models. This paper aims to explore how persons involved in R&D activities have a pattern to understand the processes. Data for this study were collected using a survey applied to directives, coordinators, technology managers, intellectual property managers, researchers, and entrepreneurs in a group of 11 universities in Medellín (Colombia) through a computational clustering analysis. The main contribution of this article is the generation of five patterns or mental models, in which the different roles linked to R&D converge, to this extent we could speak of shared mental models. One of the more significant findings that emerge from this study is that a simpler mental model with specific and relevant activities prioritised may work better than a complex one.
Keywords: 650; computational clustering; data science; innovation process; mental models; Valley of Death